2022
DOI: 10.3390/ma15155234
|View full text |Cite
|
Sign up to set email alerts
|

Wear Behavior between Aesthetic Restorative Materials and Bovine Tooth Enamel

Abstract: Tooth enamel wear occurs because of daily mastication and occlusion. This study investigated the wear behavior of bovine teeth against aesthetic restorative materials in vitro. Abrader specimens were fabricated using four tooth-colored restorative materials (zirconia, lithium disilicate glass ceramic, dental porcelain, and resin composite), with bovine tooth enamel as a control. Flattened bovine tooth enamel was used as the substrate specimen. These materials were characterized by Vickers hardness tests and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…A power analysis performed using SPSS software with hypothesized values from previous studies 3,6,7,15…”
Section: Microhardness Testingmentioning
confidence: 99%
See 3 more Smart Citations
“…A power analysis performed using SPSS software with hypothesized values from previous studies 3,6,7,15…”
Section: Microhardness Testingmentioning
confidence: 99%
“…13,14 Previous studies have reported that zirconia is harder than lithium disilicate which is generally reported to be similar or harder than porcelain. 3,6,7 Enamel is less hard than porcelain. 3,6,7,15 Previous studies have reported similar hardness for 3Y and 5Y zirconia.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Irregularities on the surface of restoration can facilitate plaque accumulation, leading to gingival inflammation and caries formation, as well as increased bacterial adhesion and surface discoloration on restorative materials (Trauth et al, 2012). Roughness could be increased after wear (Hatanaka et al, 2022) or exposure to acidic foods and drinks (Poggio et al, 2012). Previous studies have indicated that, while bleaching procedures do not appear to cause macroscopically visible changes in resin composite restorations, microscopic changes that may occur can reduce the polishability of restorations and lead to a dull and unesthetic appearance (Trauth et al, 2012;Wattanapayungkul & Yap, 2003).…”
Section: Introductionmentioning
confidence: 99%